Comparative Evaluation of Efficacy and Tolerability of Glycolic Acid, Salicylic Mandelic Acid, and Phytic Acid Combination Peels in Melasma. Issue 3 (March 2016) - Sarkar, Rashmi; Garg, Vijay; Bansal, Shivani; Sethi, Sumit; Gupta, Chitra
Abstract : BACKGROUND: Melasma is acquired symmetric hypermelanosis characterized by light-to-deep brown pigmentation over cheeks, forehead, upper lip, and nose. Treatment of this condition is difficult and associated with high recurrence rates. Chemical peels have become a popular modality in the treatment of melasma. OBJECTIVE: To compare the therapeutic efficacy and tolerability of glycolic acid (35%) versus salicylic-mandelic (SM) acid (20% salicylic/10% mandelic acid) versus phytic combination peels in Indian patients with melasma. MATERIALS AND METHODS: Ninety patients diagnosed with melasma were randomly assigned into 3 groups of 30 patients each. Group A received glycolic acid (GA-35%) peel, Group B received SM acid, and Group C received phytic combination peels. Each group was primed with 4% hydroquinone and 0.05% tretinoin cream for 4 weeks before treatment. Chemical peeling was done after every 14 days in all groups until 12 weeks. Clinical evaluation using melasma area and severity index (MASI) score and photography was recorded at every visit and follow-up was done until 20 weeks. RESULTS: There was a decrease in MASI score in all 3 groups but it was statistically significantly lower in Group A than Group C ( p = .00), and it was also statistically significantly lower in Group B than Group C ( p = .00) but there was no statistically significant difference between Groups A and B ( p = .876). Objective response to treatment evaluated by reduction in MASI scoring after 12 weeks was 62.36% reduction in GA group, 60.98% reduction in SM group, and 44.71% in phytic acid group. CONCLUSION: It is concluded that GA (35%) and SM acid peels are both equally efficacious and a safe treatment modality for melasma in Indian skin, and are more effective than phytic acid peels. Salicylic-mandelic peels are better tolerated and more suitable for Indian skin.